Marine Mammal Interactions With Fisheries: Review of Research and Management Trends Across Commercial and Small-Scale Fisheries - Jog, Ketki; Sutaria, Dipani; Diedrich, Amy; Grech, Alana; Marsh, Helene (Frontiers in Marine Science, 2022)
Marine mammal interactions with fisheries, such as bycatch and depredation, are a common occurrence across commercial and small-scale fisheries. We conducted a systematic review to assess the management responses to marine mammal interactions with fisheries. We analyzed literature between 1995 and 2021 to measure research trends in studies on direct and indirect interactions for: (i) high and low to middle-income countries, (ii) fishery operations (commercial and small-scale), and (iii) taxonomic groups. Management responses were categorized using the framework described previously in peer-reviewed studies. Marine mammal bycatch remains a major conservation concern, followed by marine mammal depredation of fishing gear. A high proportion of studies concentrated on commercial fisheries in high-income countries, with an increase in small-scale fisheries in low to middle-income countries between 1999 and 2020. The insufficient understanding of the social dimensions of interactions and the inevitable uncertainties concerning animal and human behaviors are major challenges to effective management. Despite the key role of human behavior and socioeconomics, we found only eight articles that incorporate human dimensions in the management context. Integrating social dimensions of marine mammal interactions with fisheries could help in setting pragmatic conservation priorities based on enhanced understanding of critical knowledge gaps. An area-specific adaptive management framework could be an effective tool in reducing the risk to marine mammals from fisheries by coupling technical solutions with socio-economic and political interventions. We conclude that despite the vast body of literature on this subject, a “silver bullet” management solution to marine mammal interactions with fisheries does not yet exist.